2017
DOI: 10.1080/2162402x.2017.1356143
|View full text |Cite
|
Sign up to set email alerts
|

TAP1 down-regulation elicits immune escape and poor prognosis in colorectal cancer

Abstract: The anti-tumor immune response has been shown to be of great prognostic importance in colorectal cancer (CRC) and so has the tumors ability for immune evasion. Our aim of this study was to investigate tumor factors that influence immunity. We used a gene expression array to search for potential mechanisms of tumor immune escape. One candidate gene identified was , involved in antigen presentation by MHC class I. TAP1 protein expression was evaluated by immunohistochemistry in 436 CRC patients of the Colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 44 publications
3
51
1
Order By: Relevance
“…Therefore, new trials are encouraged to further develop and verify our risk signature in standard treatment cohorts. Emerging evidence have confirmed the prognostic values of immune genes in various cancers (Patel et al, 2013;Surmann et al, 2015;Yang et al, 2015;Ling et al, 2017;Ding et al, 2018). In current study, six IRGs were identified as the risk signature.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, new trials are encouraged to further develop and verify our risk signature in standard treatment cohorts. Emerging evidence have confirmed the prognostic values of immune genes in various cancers (Patel et al, 2013;Surmann et al, 2015;Yang et al, 2015;Ling et al, 2017;Ding et al, 2018). In current study, six IRGs were identified as the risk signature.…”
Section: Discussionsupporting
confidence: 69%
“…It was found to be associated with tumor immune escape and prognosis (Leone et al, 2013). Ling et al (2017) found that the expression of TAP1 was significantly associated with infiltrative general T cells (CD3 + ), CD8 + cytotoxic T cells, M1-type macrophages, and M2-type macrophages, and the expression of TAP1 could serve as an independent prognostic factor in colorectal cancer. In term of HSP70, encoded by HSPA1B, has emerged as a promising antitumor target in various cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the nine genes, seven (NFKB1, FYN, ADIPOR2, TAP1, HSPA1A, ERAP2 and FGF18) out of them have been previously reported to be involved in the pathogenesis, progression, malignant transformation, and pathological process of immune microenvironment of READ, which are significantly correlated with patient survival and prognosis [30][31][32][33][34][35]. These previous findings have been verified the high reliability and accuracy of the bioinformatic mining results in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In different types of cancer, epigenetic and genetic alterations are most prevalent in NLRC5 among all the MHC class I-related genes and are associated with impaired expression of the MHC I pathway components and immune evasion (Yoshihama et al 2016). Accordingly, TAP1 downregulation has been shown to elicit immune escape in colorectal cancer (Ling et al 2017). Further described mechanisms of immune evasion in breast and other cancer cells involve increased programmed deathligand 1 (PD-L1) expression (Coelho et al 2017, Martinez et al 2017, stabilized PD-L1 mRNA (Glodde & Hölzel 2017) and altered PD-L1 function (Maj et al 2017) by different molecular pathways.…”
Section: Mechanisms Of Immune Suppression or Immune Escapementioning
confidence: 99%